Synthesis of nickel doped cobalt ferrite in presence of SDS with different heat treatment by co-precipitation method - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Khorrami, Saeid Abedini; Lotfi, Roshanak; Zamanian, Ali; Shabanzadeh, Parvaneh (National Institute R and D of Materials Physics, 2013)
Structural properties of nickel doped cobalt ferrite were synthesized by co-precipitation method with sodium dodecyl sulfate (SDS) as a surfactant at different temperatures. The particle size was estimated by the full width half maximum (FWHM) of the strongest X-ray diffraction (XRD) peak. The average particle size was in the range of 21-36 nm. The particles size was controlled via controlling calcination temperature which was in the range of 600 to 900°C. The morphology of nickel doped cobalt ferrite was investigated. The results showed that a well crystalline single cubic structure of nickel doped CoFe2O4 phase was formed through precipitation precursors at pH value of 11. The pH was adjusted by the use of ammonium hydroxide solution.